Comparative analysis of species composition, landscape distribution and dynamics of occurance of veals in cattle in Iraq and Dagestan - Anisimova, Elena I. (Experimental Biology and Biotechnology, 2018)
Data about species composition, landscape distribution and dynamics of occurrence of nematodes genus Thelazia Bosc, 1819 on the territories of Iraq and Dagestan are discussed. Comparative analysis of data has shown that extensiveness of cattle invasion was 10.25 % in Iraq and 14.9 % in Dagestan. Three species of veals were registered on the territories of two countries: Thelazia gulosa (Railliet et Henry, 1910), Thelazia skrjabini (Erschow, 1928) and Thelazia rhodesi (Desmarest, 1827). T. gulosa was dominant species. A long process of cattle invasion under the conditions of the all zones of Dagestan and all provinces of Iraq was revealed. Research on trofically connected with cattle pasture flies allowed to estimate their species composition and forms taking part in thelaziosis distribution. An average density of pasture flies was estimated. It was revealed, that extensiveness of invasion depends statistically reliably from density of Diptera with the time shift.